Advanced Liver Fibrosis Correlates With Impaired Efficacy of Pfizer‐BioNTech COVID‐19 Vaccine in Medical Employees. Issue 6 (11th February 2022) - Shafrir, Asher; Amer, Johnny; Hakimian, David; Milgrom, Yael; Massarwa, Muhammad; Hazou, Wadi; Imam, Ashraf; Khalaileh, Abed; Safadi, Rifaat
Abstract : The Pfizer‐BioNTech coronavirus disease 2019 (COVID‐19) vaccine has been offered to nonallergic ≥16‐year‐old Israeli adults since December 19, 2020. Data regarding factors associated with vaccine ineffectiveness are limited. The aim of this study is to assess the impact of hepatic fibrosis on the efficacy of the BioNTech vaccine. Serum severe acute respiratory syndrome coronavirus 2 spike immunoglobulins (S IgG) obtained at least 7 days following vaccination completion was correlated with the prevaccine calculated Fibrosis‐4 (FIB‐4) score among 719 employees in the Hadassah Medical Center, Jerusalem. Positive vaccine response (S IgG levels ≥ 19 AU/mL) was found in 708 of 719 individuals (98.5%). Vaccine failure (S IgG levels < 19) was found in 11 (1.5%); of these, 7 were immunosuppressed. Mean FIB‐4 available in 501 of 708 vaccine responders was 1.13 ± 0.66, mean age 51.4 ± 12.4 years (29.3% males), and mean S IgG titers 239.7 ± 86.1 AU/mL. Similar to the general population, 70.5% had normal FIB‐4 (<1.3), 26.8% undetermined FIB‐4 (1.3‐2.67), and 2.7% advanced FIB‐4 (>2.67). When divided into response subgroups, 158 of 501 individuals (30.1%) with IgG titers 19‐100 AU/mL had a mean FIB‐4 of 1.48 ± 0.82; 198 (39.5%) with IgG titers 101‐200 AU/mL had mean FIB‐4 of 1.22 ± 0.76; 83 (16.6%) with titers 201‐300 AU/mL had mean FIB‐4 of 1.04 ± 0.48; 38 (7.6%) individuals with IgG titers 301‐400 AU/ml had a mean FIB‐4 of 1.08 ± 0.63; and 121 (24.2%) with IgG titers >400 AU/mL had mean FIB‐4 of 1.18 ± 0.87. Increased FIB‐4, age, and male gender significantly correlated with lower postvaccine IgG titers ( P  < 0.001). FIB‐4 results were confirmed using FibroScan data displaying advanced fibrosis impact on weakened COVID‐19 vaccine response. Conclusion: Immune suppression, older age, male gender, and advanced chronic liver disease are risk factors for lower vaccine response. The FIB‐4 provides a simple tool to prioritize candidates for third‐dose vaccine booster.